CHOCOCHIP DRY CAKES AS A SNACK FOR DIABETES SUFFERERS - Khairunniza, Dea; Syafruddin, S (Politeknik Negeri Lhokseumawe, 2023)
ABSTRACTChoco chips are chocolate in the form of small granules, usually chocolate chips are used as decoration on cakes, pastries and so on. Generally, chocolate chips are only used as a snack and contain high levels of sugar. This research discusses how to consume chocochip snacks which have low sugar content and are safe for diabetes sufferers. The independent variables used in this research are the types of sugar in the form of palm, regular and tropical as well as the types of wheat and oat flour. This research was carried out by making dry cakes first with various variations of sugar and flour. After that, tests are carried out in the form of water, protein, carbohydrate, free fatty acid content and organoleptic tests. From the research results, it was found that the lowest content test was a sample of wheat flour with a variation of tropical sugar of 4.1%, while the chocochip cake with the highest water content was a sample of oat flour with a variation of palm sugar with a water content of 6.36%. In the protein content test, the chocochip cake with the lowest protein content was a sample of oat flour with a variety of tropical sugar with a protein content of 101.06 mg/L, while the chocochip cake with the highest protein content was a sample of wheat flour with a variety of tropical sugar with a protein content of 204 .51 mg/L. In the carbohydrate content test, the chocochip cake with the lowest carbohydrate content was a sample of wheat flour with a variety of regular sugar with a carbohydrate content of 60.17 mg/L, while the chocochip cake with the highest carbohydrate content was a sample of oat flour with a variety of regular sugar with a carbohydrate content of 109.22 mg/L. In the free fatty acid content test, the chocochip cake with the lowest free fatty acid content was a sample of wheat flour with a variety of regular sugar with a free fatty acid content of 1.01%, while the chocochip cake with the highest free fatty acid content was a sample of oat flour with a variety of sugar. sugar palm with a free fatty acid content of 1.69%. In the organoleptic test for panelists, the choco chip cake with the highest average score was in the sample with variations of oat flour and palm sugar. Key words : antidiabetes, chocolate chips, cookies